A solution-processed and low threshold voltage p-type small molecule based on indolocarbazole- and benzothiophene-fused rings. (September 2017) - Chen, Guiting; Sun, Sheng; Yang, Yong; Lan, Linfeng; Ying, Lei; Yang, Wei; Zhang, Bin; Cao, Yong
Abstract: A novel planar heteroacene, 8, 17-dihexadecyl-8, 17-dihydrobenzo[4′, 5′]thieno[2′, 3′:5, 6] indolo[3, 2- b ]benzo[4, 5]thieno[2, 3-h]carbazole (ICzDBT), was designed and synthesized. The thermal, optical, electrochemical and field-effect transistor properties were investigated systematically. The highest occupied molecular orbital energy levels ( E HOMO ) measured by cyclic voltammetry and photoelectron yield spectra were −5.15 and −5.29 eV, respectively, which are close to the work function ( WF ) of Au (∼5.2 eV). This suitable energy level alignment between the E HOMO of ICzDBT and WF of Au is favorable for hole carrier injection from the Au electrode to the ICzDBT layer. The ICzDBT showed a hole mobility as high as 0.17 cm 2  V −1  s −1 and a current on/off ratio of 1.2 × 10 6, with a very low threshold voltage of −0.8 V. Moreover, the device displayed excellent stability with little roll-off of hole mobility in air. Hence, this kind of molecule is a promising candidate for p-type organic field-effect transistors (OFETs) with high mobility and air stability. Graphical abstract: Highlights: A novel planar p-type heteroacene (ICzDBT) was designed and synthesized. The field-effect transistor properties show very low threshold voltage of −0.8 V. The ICzDBT displays highly thermal and electric stability.